2004
DOI: 10.5688/aj6805117
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Response System to Promote Active Learning in the Doctor of Pharmacy Curriculum

Abstract: BACKGROUNDColleges and schools of pharmacy have undergone major curricular changes to better prepare first-professional degree doctor of pharmacy students for practice and to enhance problem-solving skills. The use of techniques that foster active learning and critical thinking are necessary to accomplish this task. Despite increased efforts to enhance active learning, many pharmacy educators have difficulty engaging and maintaining the interest of all students in large classrooms. 1 Engaging students througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 3 publications
11
85
0
8
Order By: Relevance
“…Our findings support other pharmacy education studies that describe positive student outcomes associated with student engagement [39][40][41][42][43][44][45] and performance [3,40,46,42,43] in ARS based learning. In fact, ARS is one of the most commonly used active learning strategies in US Colleges and Schools of Pharmacy [4].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings support other pharmacy education studies that describe positive student outcomes associated with student engagement [39][40][41][42][43][44][45] and performance [3,40,46,42,43] in ARS based learning. In fact, ARS is one of the most commonly used active learning strategies in US Colleges and Schools of Pharmacy [4].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the students in our survey also reported that the i-SIDRA system promoted the clarification and understanding of concepts (median: 5). These findings are in agreement with those of other studies which report the ability of ARSs to enhance understanding of the material [46,42].…”
Section: Surveysupporting
confidence: 93%
See 2 more Smart Citations
“…42 This results in focused and effective peer-to-peer discussions when using interactive learning tools. 9,43,44 LAP allows the audience to ask and answer questions which they otherwise would not.…”
Section: Discussionmentioning
confidence: 99%